Apathy, Novelty Processing, and the P3 Potential in Parkinson’s Disease - Kaufman, David A. S.; Bowers, Dawn; Okun, Michael S.; Van Patten, Ryan; Perlstein, William M. (Frontiers in Neurology, 2016)
Parkinson’s disease (PD) is characterized by deficits in goal-directed behavior as well as mood and motivational symptoms, including apathy, depression and anxiety. The present study investigated novelty processing in PD, using event-related potentials (ERPs) to characterize electrophysiological reflections of visual novelty processing. Since apathy has been associated with decreased novelty processing (P3 potentials) in highly apathetic PD patients, we were particularly interested to see if this relationship exists in a sample of PD patients with heterogeneous levels of apathy. Non-demented patients with PD receiving dopaminergic treatment (n = 14) and healthy control participants (n = 12) completed a three-stimulus oddball task while EEG was recorded. Relative to controls, the PD patients exhibited reductions in centrofrontally distributed P3 potentials when viewing novel distracters during this task. Distracter-related P3 amplitudes evoked by novel distracters were strongly associated with apathy symptoms, even after controlling for the effects of depression, anxiety, and executive function. Executive dysfunction was also predictive of novelty related P3 processing, yet this relationship was independent from that of apathy. These findings suggest that the brain’s electrophysiological response to novelty is closely related to both motivational and cognitive symptoms in PD, even for patients whose apathy symptoms are not excessive. These results have significant implications for our understanding of non-motor symptoms in this clinical population.